2006
DOI: 10.1590/s1413-70542006000300024
|View full text |Cite
|
Sign up to set email alerts
|

Nutrientes na fitomassa de capim-marandu em função de fontes e doses de nitrogênio

Abstract: RESUMOEm pastagens manejadas intensivamente, que recebem altas doses de nutrientes, é necessário conhecer sua extração para auxiliar as recomendações de adubação. Este trabalho teve a finalidade de avaliar os nutrientes extraídos pela fitomassa de capimmarandu (Brachiaria brizantha (Hochst ex. A. Rich.) Stapf cv. Marandu) submetido a fontes e doses de N e seu efeito na recuperação aparente do N, em experimento conduzido em Latossolo Vermelho Distrófico típico, sob condições tropicais. Foram aplicadas três dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1
61

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 9 publications
(3 reference statements)
4
38
1
61
Order By: Relevance
“…This confirms the high K recycling capacity of grasses and their potential use as cover crops (Raij et al 1997). Lower K contents and accumulation in signalgrass were obtained by Primavesi et al (2006). Jack bean and pearl millet showed the lowest K contents (Table 2); however, due to great dry matter production, jack bean had higher accumulated values of K than sunn hemp and pearl millet, differing from values described in the literature.…”
Section: Discussionmentioning
confidence: 62%
“…This confirms the high K recycling capacity of grasses and their potential use as cover crops (Raij et al 1997). Lower K contents and accumulation in signalgrass were obtained by Primavesi et al (2006). Jack bean and pearl millet showed the lowest K contents (Table 2); however, due to great dry matter production, jack bean had higher accumulated values of K than sunn hemp and pearl millet, differing from values described in the literature.…”
Section: Discussionmentioning
confidence: 62%
“…The maximum content of leaf nitrogen found by Lavres Júnior & Monteiro (2002) Primavesi et al (2006), working with Marandu grass (Brachiaria brizantha), found nitrogen contents ranging from 17 to 24 g kg -1 . Nevertheless, for Piatã grass, in the present study, it was found content of up to 34 g kg -1 in the first cut, showing a higher nutritional potential, when the nitrogen fertilization is handled properly.…”
Section: Resultsmentioning
confidence: 91%
“…Primavesi et al (2006), using a combination of nitrogen and potassium fertilization on Marandu grass observed that potassium contents ranged from 28 to 35 g kg -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Lana et al (2010) observed contents of 2.80 g kg -1 for Mg and 4.12 g kg -1 for Ca with mineral fertilization in the second cut, which were significant compared with highest dose of poultry manure applied. Primavesi et al (2006) observed that Ca contents in the dry matter of Marandu grass increased, although slightly, with fertilization using ammonium nitrate.…”
Section: Resultsmentioning
confidence: 95%
“…Silva et al (2013) found linear adjustment and K content of 17.72 g kg -1 for the treatment with 20 t ha -1 of poultry manure. According to Primavesi et al (2006) and Costa et al (2009), these low K contents may be associated with the large K extraction by Marandu grass with high forage production.…”
Section: Resultsmentioning
confidence: 99%